TV Technical Operations - Ward, Peter (Routledge, 2013)
TV Technical Operations is an introduction for new entrants to the broadcast industry and is designed to prepare them for working in mainstream television by discussing essential techniques, technologies and work attitudes. The author explores: * the need to develop a professional approach * the occupational skills needed to meet deadlines, work under pressure and within budget * the importance of understanding the potential of broadcast equipment in program making * the need to keep up to date with the technique and technology * the responsibility to ensure continuity of experience and training in all craft skills that technical operators are required to work with * the need to maintain a critical appraisal of what and who influences working practices and how these influences affect production and viewers * an introduction to the basic skills needed to work as a multi-skilling technical operator in television * an introduction to broadcast equipment in general production use Peter Ward is a freelance cameraman and camerawork trainer working with international training and television consultancy. He was formerly head of cameras at Television South West.
Online resource; Title from title page (viewed January 17, 2013)
Keywords: Digital video; Television -- Handbooks, manuals, etc -- Production and direction; Television -- Terminology -- Production and direction; Television -- Production and direction -- Vocational guidance; Television -- Production and direction; Video recording -- Handbooks, manuals, etc; Video recording; Video recordings; Video art; Vidéo numérique; Télévision; Production et réalisation; Guides, manuels, etc; Télévision; Production et réalisation; Terminologie; Télévision; Production et réalisation; Orientation professionnelle; Télévision; Production et réalisation; Vidéo; Guides, manuels, etc; Vidéo; Vidéos; Art vidéo; video recordings (physical artifacts); video (discipline); video art; video recording (process); Television; Production and direction; Vocational guidance; Television; Production and direction; handbooks; Handbooks and manuals; Terminology; Guides et manuels